FAKTOR DETERMINASI TRANSFER PRICING (STUDI EMPIRIS PADA PERUSAHAAN FOOD AND BEVERAGES PERIODE 2017-2020) - Stephanie Fransisca Gabriella; Bimo Kun Dwi; Tyas Widyatiningsih; Rossje V. Suryaputri (Jurnal Magister Akuntansi Trisakti, 2022)
This study aims to examine the effect of tunneling incentives, bonus plan and firm size as instruments in detecting the company's decision to transfer pricing. The independent variables in this research are tunneling incentives, bonus plan and firm size as well as leverage and firm size as control variables. The sample was taken by purposive sampling method consisting of 60 food and beverages companies of consumer goods industry sector listed in Indonesia Stock Exchange which have reported complete financial report in period 2017-2020.  Test of hypothesis was using SPSS  25 application.  The results show that tunnelling incentive has positive significant on transfer pricing and fiirm size has weaken positive significant on transfer pricing.  Meanwhile, other independent variable bonus plan has no significant effect.